The prevalence of diabetic nephropathy in conservative hemodialysis patients of Mazandaran and Golestan, 1998 - B Heidari (Babol University of Medical Sciences, 1999)
Objective: Progressive course of diabetic nephropathy (DM), which is an important cause of death among diabetics, ultimately leads to permanent hemodialysis. DN is the most common cause of end-stage renal failure in most countries. Methods: Identification and treatment of DM predisposing factors in hemodialysis patient was done in seven provincial Mazandaran and Golestan dialysis centers of Mazandaran and Golestan, all patients who underwent permanent hemodialysis in 1998 were studied. Etiologic studies in renal failure have been conducted using the patient’s last hospital admission history. The information about diabetes provided by interview, medical examination and completion of questionnaires. Diabetes typing was done using the national diabetes data group criteria. Findings: The results show that 32 of 353 hemodialysis patients of Mazandaran and Golestan (9%) have DM. 26 of the diabetics were type 2 and the others were type 1. The average age of patients and of starting hemodialysis in type 2 diabetes were 57.5±9.4, 54±10.4 years and 38.5±9.5, 35±1 years and in type 1. Conclusion: In comparison with foreign countries the prevalence of DM in Mazandaran and Golestan is lower. The reasons for the difference may be, geographic differences in diabetes prevalence and the predisposing factors of DM, early death of patients with DM before starting hemodialysis or different criteria for choosing and introducing patients for hemodialysis.